The Conversion of Human Tissue‐Like Inflammatory Monocytes Into Macrophages. Issue 3 (11th March 2021) - Bsat, Marwa; Mehta, Heena; Rubio, Manuel; Sarfati, Marika
Abstract: Classical circulating LyC6 high murine monocytes differentiate progressively from inflammatory tissue monocytes to mature macrophages (Mϕ) after entry into gut mucosa. This protocol provides a two‐step in vitro culture method that replicates the human monocyte maturation cascade. First, purified circulating CD14 + CD16 − monocytes exposed to granulocyte‐macrophage colony‐stimulating factor (GM‐CSF), interferon gamma (IFNγ), and interleukin 23 (IL‐23) differentiate into tissue‐like inflammatory monocytes. Next, addition of transforming growth factor beta (TGFβ) plus interleukin 10 (IL‐10) promotes their maturation into tissue‐like Mϕ. Methods to sort these cells after culture are also provided. The fine‐tuning of this system might open therapeutic avenues for chronic inflammatory disorders. © 2021 Wiley Periodicals LLC Basic Protocol 1 : Isolation of human monocytes from peripheral blood Basic Protocol 2 : First step culture for generation of inflammatory monocyte‐like cells Basic Protocol 3 : Second step culture for differentiation of inflammatory monocyte‐like cells into macrophages Alternate Protocol : Sorting and culturing of inflammatory monocyte‐like cells